1998
DOI: 10.1136/oem.55.10.705
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of phenol, catechol, hydroquinone, and muconic acid by workers occupationally exposed to benzene.

Abstract: Objectives-Animal inhalation studies and theoretical models suggest that the pattern of formation of benzene metabolites changes as exposure to benzene increases. To determine if this occurs in humans, benzene metabolites in urine samples collected as part of a cross sectional study of occupationally exposed workers in Shanghai, China were measured. Methods-With organic vapour monitoring badges, 38 subjects were monitored during their full workshift for inhalation exposure to benzene. The benzene urinary metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 42 publications
4
52
0
1
Order By: Relevance
“…The urinary concentrations of phenol and hydroquinone varied widely (ie 5-to 25-fold) within a given population. [49][50][51] Some studies have reported differences in phenol levels between sexes, 54 whereas others have not. 48 Variability of phenol levels among individuals appears to be greater than the difference among males and females.…”
Section: Phenol and Hydroquinone Levels In Unexposed Individualsmentioning
confidence: 99%
See 3 more Smart Citations
“…The urinary concentrations of phenol and hydroquinone varied widely (ie 5-to 25-fold) within a given population. [49][50][51] Some studies have reported differences in phenol levels between sexes, 54 whereas others have not. 48 Variability of phenol levels among individuals appears to be greater than the difference among males and females.…”
Section: Phenol and Hydroquinone Levels In Unexposed Individualsmentioning
confidence: 99%
“…The other important factors affecting reported phenol values are variation in sampling and adjustment for gravity and creatinine. Phenol levels are typically reported as a concentration, mass per mass creatinine, or total mass excreted in 24 h. Data from Refs 47,50,51,54,57,58,75,107,108. flora. Below we discuss these sources and also describe additional host and environmental factors that affect the variability of the background levels of the phenolic compounds.…”
Section: Sources Of Phenol and Hydroquinone In 'Unexposed' Peoplementioning
confidence: 99%
See 2 more Smart Citations
“…The major sources of benzene in ambient air of urban areas are car exhaust and evaporation loss during the handling, distribution and storage of petrol 1,2) . Urinary metabolites that might serve as indices of occupational or environmental exposure to benzene include phenol, hydroquinone, trans, trans-muconic acid (t,t-MA), and S-phenyl mercapturic acid [3][4][5] . Of these, urinary t,t-MA concentration is recognized as a reliable biomarker which is relatively convenient to measure 6) .…”
Section: Introductionmentioning
confidence: 99%